The Use of Upper-Body Intermittent Sequential Pneumatic Compression Arm Sleeves on Recovery From Exercise in Wheelchair Athletes. (January 2021) - Oliver, Alison; Driller, Matthew
Abstract : Objective: The aim of the current study was to investigate the efficacy of an upper-body intermittent sequential pneumatic compression device on recovery after wheelchair team sport activity. Design: Eleven well-trained wheelchair basketball and rugby athletes (male, 8; female, 3; mean ± SD age = 33 ± 10 yrs) performed a series of performance measures pre-exercise, postexercise, and postrecovery (grip strength, pressure-to-pain threshold, medicine ball throw, wheelchair sprints, repeated sprints). Subjective muscle soreness and fatigue measurements were taken at the same time points as performance tests, with an additional 24-hr postrecovery measure. Participants completed two recovery trials, separated by 1 wk, of either passive recovery (control) or 20 mins of wearing recovery arm sleeves (intermittent sequential pneumatic compression) applied to both arms. Results: No statistically significant differences were found between trials for any of the performance or perceptual measures ( P > 0.05). However, effect size analysis revealed a moderate decrease ( d = −0.67) from postexercise to postrecovery for muscle fatigue in favor of intermittent sequential pneumatic compression. A large decrease ( d = −0.96) in muscle soreness was also found after exercise to 24 hrs after recovery in favor of intermittent sequential pneumatic compression over control. Conclusions: Intermittent sequential pneumatic compression may provide some benefit for perceptual recovery measures immediately after and 24 hrs after a high-intensity wheelchair activity with negligible effects on performance recovery.